Ads
related to K
Sort by
- Relevance
- |Time
K word ?? Got me I know the F word and the C word And the B words but the K word what Kitten ?
6 Answers · Society & Culture · 19/10/2008
Goal: To get "k" isolated by itself. a.) 0 = 14 + k In order to isolate... so that the 3.3 on the variable side will turn into 0 and will not count. -0.8 = k + 3.3 -0.8 - 3.3 = k + 3.3 - 3.3 -4.1 = k + 0 Since the zero does...
3 Answers · Science & Mathematics · 16/06/2011
k(x) = x² - 6 k(x - 1) = (x - 1)² - 6 k(x - 1) = x² - 2x + 1 - 6 k(x...2(2x + 4) + 4 h(h(x)) = 4x + 8 + 4 h(h(x)) = 4x + 12 h(x) = 2x + 4, k(x) = x² - 6 h(k(x)) = 2(x² - 6) + 4 h(k(x)) = x²...
2 Answers · Science & Mathematics · 21/09/2012
(k - 2)x^2 + (k - 5)x - 5 = 0 The roots are equal if the discriminant... discriminant, b^2 - 4ac, evaluated as follows: (k - 5)^2 - 4(k - 2)(-5) And we want this to be equal to zero. (k...
3 Answers · Science & Mathematics · 06/12/2008
In ecology, K selection theory relates to the selection of combinations of ...to drive evolution in one of two generalized directions: r- or K-selection. These terms, r and K, are derived from...
3 Answers · Science & Mathematics · 14/10/2009
k ∫ (2kx - x^2)dx = 18 0 ....................k (kx^2 - x^3/3) | = 18 ....................0 k(k^2) - k^3/3 - (k(0^2) - 0^3/3) = 18...
1 Answers · Science & Mathematics · 02/05/2011
...e^(kx) - e^(-kx) ] / [ e^(3x) + e^(-3x) ] When x is large and assume k >= 0 sinh(kx) / cosh(3x) ≈ e^(kx) / e^(3x) = e^(x(k - 3)) For sinh(kx...
1 Answers · Science & Mathematics · 21/02/2019
-k^3 + k^2pk - pk +p^2 = 0 p^2 + pk (k^2 - 1) - k^3 = 0 Solve for p by using the quadratic... up my own problem: The second term "k^2pk" looks very strange, so I will suppose it ...
1 Answers · Science & Mathematics · 06/10/2009
k(k+1)(2k+1)/6 must be divisible by 100 means k(k+1)(2k+1) divisible by 600 which is 5x5x2x2x2x3 2k+1 is odd, and only one of k or k+1 can be even so you need k or k+1 divisible by 8 one of k, k+1, and 2k+1 will always be divisible...
4 Answers · Science & Mathematics · 18/12/2013
(k-1)x^2+2x-(k-3)=0 suppose k-1=a and k-3=b so,a-b=k-1-k+3=2 so the equation becomes ax^2+(a-b)x-b=0 => ax^2+ax-bx-b=0 =>ax(x+1)-b(x+1)=0 =>(ax-b)(x-1)=0 x=-1 or x=b/a=(k-3)/(k-1)
5 Answers · Science & Mathematics · 31/01/2011
Ads
related to K